SÍZÍQLÍ TENLEMELER SISTEMASÍNÍŃ BAZÍBIR QOLLANÍWLARÍ - Asqarov, M.; Koshkarbaeva, R.; Ubaydullaeva, A. (SCIENCE and SOCIETY, 2022)
The article presents the solutions of problems that can be solved by a system of algebraic equations. These solution methods are also used in solving geometric problems. Examples of a system of high-order equations have been developed. There are examples of solutions to problems using the method of matrix and determinants.